2019
DOI: 10.7759/cureus.4947
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Pyelonephritis Causing Renocolic Fistula Presenting as Symptomatic Anemia

Abstract: Renocolic fistula is a rare clinical finding that is most commonly iatrogenic after surgical intervention. Herein, we present a case of renocolic fistula secondary to xanthogranulomatous pyelonephritis (XGP) with a subtle presentation as anemia. A 40-year-old female was found to have a hemoglobin of 6.5 g/dL after presenting for worsening fatigue. A urinalysis was remarkable for numerous white blood cell (WBC), positive bacteria, and nitrite. As part of her anemia workup, an esophagogastroduodenoscopy (EGD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…An array of complications of XGP have been described which are often secondary to involvement of adjacent organs. In children, these complications include abscesses involving the psoas muscle [ [57] , [58] , [59] ] or perinephric spaces, fistulas including nephrocutaneous [ 60 , 61 ], nephroduodenal [ 62 ], nephrocolonic [ 25 , 61 , 63 ] and even nephrobronchial [ 64 ]. There have also been reports of concomitant liver lesions [ 65 ], bronchiectasis [ 66 ] and associated renal vein thrombosis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…An array of complications of XGP have been described which are often secondary to involvement of adjacent organs. In children, these complications include abscesses involving the psoas muscle [ [57] , [58] , [59] ] or perinephric spaces, fistulas including nephrocutaneous [ 60 , 61 ], nephroduodenal [ 62 ], nephrocolonic [ 25 , 61 , 63 ] and even nephrobronchial [ 64 ]. There have also been reports of concomitant liver lesions [ 65 ], bronchiectasis [ 66 ] and associated renal vein thrombosis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of extra-renal extension can be profound, with reported cases of pancreatic, splenic and hepatic infiltration with abscess formation, cutaneous, colonic and duodenal fistulae and rib osteomyelitis also described. [10][11][12][13][14][15] Very rare instances of renal amyloidosis secondary to XGP have been reported. 16-18.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Extra-renal extension including collections and fistulae are well depicted on CT, which permits demarcation of the extent and boundaries of the inflammatory process, determining if it is confined to the kidney (focal/segmental or disseminated) (Figure 5) and, in the presence of extrarenal extension, if it is confined to the perinephric or pararenal spaces and/or if it infiltrates adjacent tissues and viscera. [10][11][12][13][14][15] A case series of 11 patients with XGP found that 10 patients (91%) had extra-renal extension, three of whom (27%) had direct extension into adjacent structures including iliopsoas muscle, abdominal wall and spleen. 37 CT facilitates staging as per Malek et al as follows: 26 Stage 1: Confined to renal parenchyma.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Xanthogranulamatous pyelonephritis (XGPN) is a rare cause of chronic renal disease, characterized by suppuration and accumulation of lipid-laden macrophages in the renal parenchyma [ 1 ]. A really uncommon sequela is the renocolic fistula, which is usually a consequence of primary bowel pathologies [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%